Peran Pemerintah-Masyarakat dalam Pembangunan Desa Sedatigede Kecamatan Sedati Kabupaten Sidoarjo - Rizky A. Prasojo; Luluk Fauziah (Universitas Muhammadiyah Sidoarjo, 2015)
This study aimed to describe the role of government-community on the development in the Sedati Gede Village, Sidoarjo Regency and its supporting and inhibiting factors. This research used qualitative descriptive method. The informants in this research are Head Village (as key informan), village government, Karang Taruna and citizen. Technique data is collected by triangulation (combined), data analysis is inductive, and qualitative research results further emphasize the significance rather than generalization. The results showed that the government's role in the development of Sedatigede village was quite good and balanced. Their cooperation was mutualistic which the parties involved in understanding the position and role in rural development. The village government got the role in facilitating community and provides good guidance to the public about the purpose of the development to be carried out. Society plays a role in contributing ideas, power, and material in succession of development. Meanwhile, the supporting factors in this cooperation used human society approach and they had a good understanding of the position and its role in development. In addition, the inhibiting factor is the lack of public awareness on environmental hygiene as well as the persistence of the notion that the government was subordinate to the people and objects in development supervision.